RELATIONSHIP OF ARM MUSCLE STRENGTH, LEG POWER AND FLEXIBILITY TO SMASH ACCURACY IN BADMINTON ATHLETES AT PB INDO CAFE MEDAN IN 2020 - Muhammad Idris Siregar; Dewi Endriani (Indonesia Sport Journal, 2020)
This study aims to determine the correlation of arm muscle strength (X1), leg muscle power (X2) and flexibility (X3) to the badminton smash ability (Y) in badminton athletes at PB Indocafe Medan in 2021. The results of the first hypothesis analysis, showed tcount < ttable where (1.006 <1.83) so it was concluded that there was no significant correlation of arm muscle strength to badminton smash ability. The results of the second hypothesis analysis, showed tcount < ttable where (1,395<1,83) so that it was concluded that there was no significant correlation of leg muscle power on badminton smash ability. The results of the third hypothesis analysis, showed tcount < ttable where (0.219 <1.83) so it was concluded that there was no significant correlation of flexibility with badminton smash ability. The results of the analysis of the fourth hypothesis, arm muscle strength (X1), leg muscle power (X2) and flexibility (X3) on badminton smash ability (Y) show a correlation coefficient of 0.844 which has a very strong correlation. The coefficient of determination of 71.2% explains that arm muscle strength, leg muscle power, and flexibility have a simultaneous influence on badminton smash ability by 71.2% while 28.8% is influenced by other variables. The magnitude of Fcount = 4.944 while Ftable = 4.46. In the hypothesis testing criteria it is stated that F count > F table at (4.944 > 4.46). So it can be concluded that there is a significant correlation of arm muscle strength, leg muscle power, and the flexibility of badminton smash abilities in badminton athletes at PB Indocafe Medan in 2020.Keywords: Smash, Strength, Power, Flexibility